The human stain - Roth, Philip (Houghton Mifflin, 2000)
Coleman Silk is a respected professor at a New England college who suddenly finds his life unraveling after a comment he makes about some African-American students is misinterpreted as a racial slur. As the scandal heats up, Nathan Zuckerman, a writer researching a biography of Silk, begins to dig deeply into Silk's life. Eventually, matters are made worse when Coleman's affair with a young married janitor named Faunia Farley is exposed. But amid the controversy, Silk must struggle to keep his greatest secret, a secret he's held for the majority of his life, from becoming made public.